Changing haemodynamics in patient with papillary muscle dysfunction. Issue 4 (April 1975) - Markiewicz, W; Amikam, S; Roguin, N; Riss, E
Abstract : A patient with papillary muscle disease caused by myocardial infarction was studied before and after injection of phenylephrine. The pulmonary wedge pressure was normal at rest. However, pressures and murmur changes, occurring spontaneously and after injection of phenylephrine, suggested that intermittent severe mitral regurgitation contributed significantly to the recurrent episodes of acute left heart failure presented by this patient.